2013
DOI: 10.1007/s10803-013-1841-8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings of a Telehealth Approach to Parent Training in Autism

Abstract: Telehealth or online communication technologies may lessen the gap between intervention requirements for children with autism spectrum disorders (ASDs) and the available resources to provide these services. This study used a video conferencing and self-guided website to provide parent training in the homes of children with ASD. The first eight families to complete the 12-week online intervention and three-month follow up period served as pilot data. Parents' intervention skills and engagement with the website,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
345
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(370 citation statements)
references
References 37 publications
19
345
1
5
Order By: Relevance
“…One study included two parent-child dyads, 11 and the other study involved eight parent-child dyads. 4 Vismara et al 4 reported that all eight of the parents in their study were married, and at least one parent had a college or post-college education. It was reported that the parents had an annual income of between US $16,000 to over US $100,000.…”
Section: Participant Characteristicsmentioning
confidence: 93%
See 4 more Smart Citations
“…One study included two parent-child dyads, 11 and the other study involved eight parent-child dyads. 4 Vismara et al 4 reported that all eight of the parents in their study were married, and at least one parent had a college or post-college education. It was reported that the parents had an annual income of between US $16,000 to over US $100,000.…”
Section: Participant Characteristicsmentioning
confidence: 93%
“…4,11 One conducted a proof-of-concept pilot study in 2010 to determine the feasibility of using remote technology in parent training in EI for autism within a home setting. 11 This research team compared two models of service delivery for two preschool-aged subjects with autism that specifically targeted strategies aimed at increasing the children's attention and motivation, turn-taking routines, initiating and responding to joint attention, communication, using pictures and objects, and imitation.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations